A New Low-Cost Plastic Solar Collector - Juanico, Luis Eduardo (2013)
An innovative solar collector based on a long plastic hose that is connected directly in series from the district water grid to consumption is presented. It takes advantage of plastic tubing to develop a simple self-construction collector that costs about 70 dollars for a one-family unit. In addition, due to its solar-pond configuration, it could achieve a good thermal performance, as it was demonstrated by modeling.